2016
DOI: 10.17129/botsci.682
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative and reproductive tree phenology of ecological groups in a tropical dry forest in central Veracruz, Mexico

Abstract: Background Tree phenology has been related to abiotic and biotic factors that trigger and regulate phenological patterns. Question We investigated whether tree species classified into ecological groups of species of successional status (late-, early-successional tree species) and seed dispersal mode (anemochory, autochory, zoochory) would display different phenological patterns. Study site and dates A tropical dry forest in eastern Mexico; November 2007 to September 2010. Methods We monthly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The strongly seasonal vegetative activity, with leaf fall and leaf budding concentrated in the dry season, found here is similar to the pattern found by other studies conducted in deciduous forests around the world (Frankie et al1974;Reich & Borchert 1984;Morellato 1992;Justiniano & Fredericksen 2000;Singh & Kushwaha 2016;Williams-Linera & Alvarez-Aquino 2016). Previous studies in deciduous forests of Brazil also found marked seasonality, with clear leaf fall in the drier period of the year (Griz & Machado 2001;Ragusa-Netto & Silva 2007;Vasconcelos et al 2010;Dalmolin et al 2015).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The strongly seasonal vegetative activity, with leaf fall and leaf budding concentrated in the dry season, found here is similar to the pattern found by other studies conducted in deciduous forests around the world (Frankie et al1974;Reich & Borchert 1984;Morellato 1992;Justiniano & Fredericksen 2000;Singh & Kushwaha 2016;Williams-Linera & Alvarez-Aquino 2016). Previous studies in deciduous forests of Brazil also found marked seasonality, with clear leaf fall in the drier period of the year (Griz & Machado 2001;Ragusa-Netto & Silva 2007;Vasconcelos et al 2010;Dalmolin et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Except for flower buds of anemochoric species and flowers at anthesis of zoochoric species from both areas, and flowers at anthesis of anemochoric species at SDF, flowering was related to all climatic variables, influencing the onset of phenophases months prior and in the month of their occurrence. The relationship between flowering and climatic factors has also been documented for other seasonal tropical ecosystems, such as the deciduous forests of Mexico (Cortés-Flores et al 2017), and the Cerrado (Batalha & Martins 2004;Pirani et al 2009;Azevedo et al 2014), and the pattern found by dispersal strategy is similar to that found by Williams-Linera & Alvarez-Aquino (2016). The species in these forests are mainly regulated by rainfall and soil water availability, which would be the main and essential causes of flowering by species at the community level, while the presence of pollinators and dispersers would play a small role in an environment poor in species and with the predominance of anemochoric seeds (Borchert et al 2004).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The phenology of the forest was studied for three years before the hurricane (Williams-Linera and Álvarez-Aquino, 2016). Leafing patterns remained similar before and after the hurricane, but at community level, the defoliation caused by Hurricane Karl affected the seasonality timing of leaf fall and the community remained leafless for a month.…”
Section: Discussionmentioning
confidence: 99%